Voluntary Participation in Forensic DNA Databases: Altruism, Resistance, and Stigma - Machado, H (2016)
The public’s understanding of forensic DNA databases remains undertheorized and few empirical studies have been produced. This article aims to address this omission by exploring the answers to an open-ended question taken from an online questionnaire regarding the reasons for individuals’ voluntarily accepting or refusing to allow their DNA profile to be included in the Portuguese forensic DNA database. The analysis is undertaken from the perspective of biological citizenship and the simultaneous empowering and disempowering effects of surveillance. The results indicate a pragmatic ethical framework that is linked to the cultural and emotional elements of altruism, resistance, stigma, and social representations of what is beneficial or harmful to the individual and to society. These subjectivities are anchored in commonplace images and metaphors for genetics, DNA, and forensic science that circulate in the messages transmitted by the media which pervade everyday life; hierarchies of trust in science and the justice system; and moral categories associated with the individual self-judgment in relation to crime, surveillance, and social order.